2019
DOI: 10.3390/condmat4030066
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy X-Ray Compton Scattering Imaging of 18650-Type Lithium-Ion Battery Cell

Abstract: High-energy synchrotron X-ray Compton scattering imaging was applied to a commercial 18650-type cell, which is a cylindrical lithium-ion battery in wide current use. By measuring the Compton scattering X-ray energy spectrum non-destructively, the lithiation state in both fresh and aged cells was obtained from two different regions of the cell, one near the outer casing and the other near the center of the cell. Our technique has the advantage that it can reveal the lithiation state with a micron-scale spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…On the other hand, the use of high-energy X-ray scattering at synchrotron radiation facilities has enabled the study of the electronic wavefunctions associated with redox processes by means of Compton scattering [9,[15][16][17]. An advantage of X-ray Compton scattering is that it can be effectively applied to commercial batteries, thanks to the high penetration power of high-energy X-rays [18,19]. In addition, the large reciprocal space range accessible to high-energy X-rays allows acquiring total scattering data for the analysis of the pair distribution function to study battery materials having short-range order only [20].…”
Section: Advanced Battery Characterisationmentioning
confidence: 99%
“…On the other hand, the use of high-energy X-ray scattering at synchrotron radiation facilities has enabled the study of the electronic wavefunctions associated with redox processes by means of Compton scattering [9,[15][16][17]. An advantage of X-ray Compton scattering is that it can be effectively applied to commercial batteries, thanks to the high penetration power of high-energy X-rays [18,19]. In addition, the large reciprocal space range accessible to high-energy X-rays allows acquiring total scattering data for the analysis of the pair distribution function to study battery materials having short-range order only [20].…”
Section: Advanced Battery Characterisationmentioning
confidence: 99%
“…Previous studies of cathode materials 20,21 have demonstrated the efficacy of Compton scattering spectroscopy toward unravelling the relationship between the key battery performance characteristics and the nature of the electronic orbitals involved in Li intercalation reactions. Merits of x-ray Compton scattering over the standard techniques are enhanced penetration depth and high bulk-sensitivity, which in turn allow in situ and operando measurements of batteries [22][23][24][25] . Since the Compton cross section 26 is very small even at 100 keV, radiation damage is usually negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a new analytical technique was developed using the line shapes of Compton scattered X-rays (S-parameter) [17]. The S-parameter analysis has successfully revealed the Li concentration in commercial batteries [18][19][20][21]. Recently, the CSI technique has achieved two-dimensional imaging with a combination of a pinhole and a two-dimensional X-ray detector, which enables high-speed imaging of a two-dimensional cross section of an object [22].…”
Section: Introductionmentioning
confidence: 99%